Playful Science Investigations in Early Childhood A Longitudinal Case Study - Moeed, Azra.; Dobson, Stephen; Saha, Sankari (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book showcases a case study of the development of a generalist early childhood education (ECE) teacher into a confident and competent teacher of science in early childhood with support from a mentor. It argues that with guided mentoring, and later, timely support of a mentor as and when required, ECE teachers can deliver the curriculum, teach science by providing opportunities to explore and then build on children's interest through intentionally planned activities, dialogue, and discourse. It presents a comprehensive literature review and research design including theoretical frames and methodology. It includes a chapter on teacher development and discusses different approaches to science investigations practiced by the teacher in the case study. The book provides evidence of children's science learning and presents the findings as response to research questions. It also includes a model of teaching as inquiry in the context of early childhood education.
Chapter 1: Playing Teaching and Learning through Science Investigations -- Chapter 2: Research Design and Methodology -- Chapter 3: Teaching Science in Early Childhood -- Chapter 4: Children Playing and Learning to Investigate -- Chapter 5: Discussion of Emerging Themes -- Chapter 6: Conclusion, and Final Thoughts. .
Keywords: Education; Children; Science -- Study and teaching; Teachers -- Training of; Childhood Education; Science Education; Teaching and Teacher Education